Living Donor Uterus Transplantation: A Single Center's Observations and Lessons Learned From Early Setbacks to Technical Success. Issue 11 (23rd May 2017) - Testa, G.; Koon, E. C.; Johannesson, L.; McKenna, G. J.; Anthony, T.; Klintmalm, G. B.; Gunby, R. T.; Warren, A. M.; Putman, J. M.; dePrisco, G.; Mitchell, J. M.; Wallis, K.; et al.
Abstract : Uterus transplantation is a vascularized composite allograft transplantation. It allows women who do not have a uterus to become pregnant and deliver a baby. In this paper, we analyze the first five cases of living donor uterus transplantation performed in the United States. The first three recipients lost their uterus grafts at days 14, 12, and 6, respectively, after transplant. Vascular complications, related to both inflow and outflow problems, were identified as the primary reason for the graft losses. Two recipients, at 6 and 3 mo, respectively, after transplant, have functioning grafts with regular menstrual cycles. Ultimate success will be claimed only after a live birth. This paper is an in‐depth analysis of evaluation, surgical technique, and follow‐up of these five living donor uterus transplants. The lessons learned were instrumental in allowing us to evolve from failure to technical and functional success. We aim to share our conclusions and build on knowledge in the evolving field of uterus transplantation. Abstract : This analysis of the first five living donor uterus transplantations in the United States and the lessons learned regarding surgical technique and postoperative follow‐up could facilitate the transition from initial failure to technical and functional success.